50 years journal of mathematical biology - Hillen, Thomas; Marciniak-Czochra, Anna (Journal of mathematical biology, 2025)
The year 2024 marked the 50th anniversary of the Journal of Mathematical Biology. The journal was founded in 1974 with the vision to build a platform for advanced mathematical methods as they are applied and developed for biological problems. What began as a small journal for a specialized group of experts has grown into a flag-ship journal of a large and ever expanding field. We celebrate this occasion with a Special Collection of papers from our Associate Editors and our past and present Editors in Chief to showcase the state of the art and stimulate interesting new research directions in Mathematical Biology.
Gesehen am 22.01.2026